Contribution to new solutions of instrumentation of Civil structures for continuous dynamic monitoring - Álvaro Cunha (2019)
This paper describes the work developed by CONSTRUCT - ViBest research group in the area of new solutions of instrumentation of Civil Structures aiming its long term dynamic monitoring. It identifies the main challenges in this area, and focus the discussion around power options and data transmission solutions. The architecture of the developed measurement systems is described, and a few practical examples of monitoring of bridges is presented. (c) 2019 9th ECCOMAS Thematic Conference on Smart Structures and Materials, SMART 2019. All rights reserved.